1983
DOI: 10.1111/j.1600-0773.1983.tb01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP in Urine, Kidney and Liver Following Long‐term Administration of Fluoride to Rats

Abstract: Rats were exposed to fluoride (F) for up to 8 weeks through the drinking water containing 100 p.p.m. F. Urine samples were regularly collected, together with tissue samples of liver and kidney at termination. All samples were assayed for cyclic AMP. No F-effect was found on liver or kidney levels of cyclic AMP. In the urine from the F-exposed rats there was an overall increase in the cyclic AMP concentration, but a decreased or unaffected 24 hrs urinary excretion of cyclic AMP. However, the F-exposed rats exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1986
1986
1990
1990

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Our results are therefore in general agreement with those of OPHAUG HoNGSLO et al (11). Our results are therefore in general agreement with those of OPHAUG HoNGSLO et al (11).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are therefore in general agreement with those of OPHAUG HoNGSLO et al (11). Our results are therefore in general agreement with those of OPHAUG HoNGSLO et al (11).…”
Section: Discussionsupporting
confidence: 93%
“…For example, fluoride may in higher doses cause a urinary concentration defect in rats (16,17) and man (18). However, in a recent study HONGSLO et al (11) found no effect on tissue content or urinary excretion of cyclic AMP following a similarly longterm treatment but with higher doses of fluoride. The plasma fluoride levels required seem to be in the range of 500-1000 ng/ml (20-50 |iM) (18,19).…”
Section: Discussionmentioning
confidence: 89%
“…172 Rats exposed to high concentrations of fluoridated drinking water (100 mg/ 1) for up to 8 weeks achieved blood fluoride levels of 0.12 mg/ 1, but exhibited no change in adenylate cyclase activity as evidenced by urinary concentrations or the daily excretion of cyclic AMP. 173 Squirrel monkeys were administered distilled water containing fluoride at 0, 1, or 5 mg/1 for 18 months. 174 The central nervous system, liver, and kidneys were examined histochemically.…”
Section: E Effects On Cellular Enzyme Activitiesmentioning
confidence: 99%